Empowering the Pipitan Lestari Sejahtera Waste Bank in Food Waste Management to Promote Environmental and Economic Sustainability - Setyadi, Sugeng; Sirajuddin, Sirajuddin; Syaifudin, Rizal; Desmawan, Deris; Mangara, Togi Haidat (MOVE: Journal of Community Service and Engagement, 2025)
This community service program was carried out in Kampung Wisata Pipitan with the aim of enhancing local community capacity in managing food waste through the empowerment of Bank Sampah Pipitan Lestari Sejahtera. The activities included socialization, technical training on bokashi composting, packaging design workshops, and digital marketing practices using a participatory approach. The results demonstrated improved knowledge and skills among participants in processing organic waste into marketable compost, the emergence of new entrepreneurial initiatives, and the development of collective awareness regarding sustainable waste management. The program concludes that integrating appropriate technology with active community participation provides a practical solution to reduce food waste while simultaneously creating new local economic opportunities.